The Naming of Kazan River, Nunavut, Canada - Sikstrom, C.B. (ARCTIC, 2012)
The Kazan River in Nunavut was designated as a Canadian National Heritage river in 1990, but the reasons for its naming and the meaning of its name are unclear. The Canadian Geographical Names Data Base gives a different definition for another Kazan River and lake located near Île-à-la-Crosse, Saskatchewan. There is also a Mont de Kazan, Quebec, named for the Kazan Cathedral in Kazan, Tatarstan, Russia. After examining the records of the Roman Catholic missionary Oblates of Mary Immaculate (OMI) and the autobiographical notes and journals of J.B. Tyrrell, who first mapped the Kazan River in 1894, I conclude that “Kazan” was intended to mean “kasba” (‘white partridge’ in the Dene/Chipewyan language). Kasba is also the name of the lake at the river’s headwaters. The reasons for the river name change from Kasba (on an 1892 Dene sketch map labeled by Tyrrell) to Kazan (on other Dene sketch maps labeled by Tyrrell in 1894) may be linked to the ministrations of OMI members who set up missions at Île-à-la-Crosse and Brochet in the mid-19th century. They likely named features near their missions to honour their faith and further their baptizing efforts. The similar sounds of Kasba and Kazan may have encouraged the naming. It is certain, however, that J.B. Tyrrell gave a new name to the river, and so changed the map of Canada. La rivière Kazan, au Nunavut, fait partie du Réseau des rivières du patrimoine canadien depuis 1990, mais les origines et la signification de son nom ne sont pas claires. La Base de données toponymiques du Canada confère une définition différente à une autre rivière Kazan et à un lac situés près d’Île-à-la-Crosse, en Saskatchewan. Il existe également un mont de Kazan, au Québec, nommé ainsi en l’honneur de la cathédrale de Kazan à Kazan, dans le Tatarstan, en Russie. Après avoir étudié les dossiers des missionnaires catholiques romains des Oblats de Marie Immaculée (OMI) de même que les notes et journaux autobiographiques de J.B. Tyrrell, qui a été le premier à cartographier le rivière Kazan en ...